Pertumbuhan Ayam Ras Pedaging Yang Diberi Ransum Mengandung Tepung Limbah Bulu Ayam - Agung Raditya Widiana; Yan Tonga; Ni Ketut Mardewi (GEMA AGRO, 2020)
The provision of adequate quality and quantity rations is expected to increase the productivity of broiler chickens. One effort to improve ration quality is to add chicken feather flour in the making of rations, because chicken feather flour is rich in crude protein. The purpose of this study was to determine the effect of giving chicken feather flour in broiler rations aged 2-5 weeks to the growth of broiler chickens and to find out how much the level of chicken feather flour can give the results of body weight gain, final body weight, feed consumption and feed conversion. best. This study uses a completely randomized design (CRD) with 4 treatments and 3 replications. Each test used 4 CP 707 broilers aged 2 weeks with homogeneous body weight. The four treatments were ration without chicken feather content as a control and ration containing chicken feather flour 2%, 4%, and 6%. The parameters observed were body weight gain, final body weight, feed consumption, and FCR (Feed Conversion Ratio). The data obtained were analyzed by analysis of variance. If between treatments showed a real effect, then proceed with the smallest real distance test from Duncan (Steel and Torie, 1989). From the results of this study it can be concluded that the provision of chicken feather flour in broiler chicken rations had a significant effect on body weight gain and final body weight, but gave no significant effect on initial body weight, FCR and ration consumption.